Analysis of combat sports players' injuries according to playing style for sports physiotherapy research - Noh, J.-W.; Park, B.-S.; Kim, M.-Y.; Lee, L.-K.; Yang, S.-M.; Lee, W.-D.; Shin, Y.-S.; Kim, J.-H.; Lee, J.-U.; Kwak, T.-Y.; Lee, T.-H.; Kim, J.-Y.; et al. (Journal of Physical Therapy Science, 2015)
[Purpose] This study describes the characteristics of injuries in strike and non-strike combat sports, and the results are intended for use in the area of sports physiotherapy research. [Subjects and Methods] The study was conducted on 159 athletes involved in a variety of combat sports. The participants included elite college players of the following sports: judo (47), ssireum (19), wrestling (13), kendo (30), boxing (16), and taekwondo (34). Of the participants, 133 were male and 26 were female. In the case of ssireum and boxing, all of the athletes were male. [Results] In the case of the combat sports, the types of injury and injured regions differed according to playing style. Dislocation and injuries to the neck, shoulders, and elbows were more frequent in the non-strike sports, while injuries to the wrists and hands were more frequent in the strike sports. There was a high incidence of sprains, strains, bruises, and injuries to the lower limbs in both groups. [Conclusion] We suggest that the characteristics of injuries in combat sports differ according to playing style, and our study will therefore provide physical therapists and researchers with information that can be used to prevent injury.